Non-coding sRNAs regulate virulence in the bacterial pathogen Vibrio cholerae - Bardill, J. Patrick (Landes Bioscience, 2012)
Vibrio cholerae is the waterborne bacterium responsible for worldwide outbreaks of the acute, potentially fatal cholera diarrhea. The primary factors this human pathogen uses to cause the disease are controlled by a complex regulatory program linking extracellular signaling inputs to changes in expression of several critical virulence genes. Recently it has been uncovered that many non-coding regulatory sRNAs are important components of the V. cholerae virulence regulon. Most of these sRNAs appear to require the RNA-binding protein, Hfq, to interact with and alter the expression of target genes, while a few sRNAs appear to function by an Hfq-independent mechanism. Direct base-pairing between the sRNAs and putative target mRNAs has been shown in a few cases but the extent of each sRNAs regulon is not fully known. Genetic and biochemical methods, coupled with computational and genomics approaches, are being used to validate known sRNAs and also to identify many additional putative sRNAs that may play a role in the pathogenic lifestyle of V. cholerae.